Changes in Polish Agriculture in the Period 2002-2010 in the Light of Central Statistical Office Census Data - Komorowska, Dorota (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2014)
According to the latest National Agricultural Census 2010, in comparison with the previous one of 2002, the number of farms decreased by almost one fourth but is still very big, which results from a large number of small farms. For this reason, more than half of land resources belong to small and medium-sized farms. This translates into the efficiency of land, labour and capital in agriculture. It has impact on the competitiveness of our agriculture, because large and very large farms are more competitive in terms of bargaining power on the agri-food market. In the period between censuses, the number of people working in agriculture increased, which is a consequence of the difficult situation on the labour market, especially in rural areas. The excessive labour resources in agriculture hamper the change of farm size structure. Advantageous changes obtained during this period are the improvement of agricultural equipment of farms and an increase in the scale of production of each of the products produced on farms, which undoubtedly improves the competitiveness of our farms.